How to apply social sciences to design research. : A case study beyond the master class. - Rojo Ojados, Ana Belen (Design/Arts/Culture, 2025)
This article introduces the members involved in design teachings in a research proposal whose main objective is to present, from the disciplines of anthropology, philosophy, sociology, art history and cultural studies, teaching experiences related to the qualitative and quantitative analysis of the impact that classical social disciplines (sociology, ethnography, consumption and trend) are having in the final degree projects produced in higher design studies. The analysis of these methodologies, from the social sciences, starts from these research to advance a "stage of the question" that can also be present in the final degree works of other studies related to the arts and design in general.